Ageing and Health in the Digital Society: Challenges and Opportunities - Bobrowicz-Campos, E.; Matos, A. P. M. (Exploring the Role of ICTs in Healthy Aging, 2020)
This chapter describes the innovative solutions generated by the digital society in the field of health and reflects on the effectiveness of the mechanisms implemented in the last decade to increase the adoption of these solutions by the aged population. This reflection begins with the analysis of the digital divide-related issues, relying on the assumption that the lack of a joint multi-stakeholder effort to reduce existing differences in access to digital resources may result in deepening inequality in health. The opportunities and risks for ageing and health in the digital era are presented considering different healthcare purposes, contexts, and end-users' perspectives. Finally, the recommendations to maximize the impact of strategic actions to increase digital literacy and to reinforce digital engagement are presented.